2018
DOI: 10.3390/catal8120657
|View full text |Cite
|
Sign up to set email alerts
|

Earth-Abundant Electrocatalysts in Proton Exchange Membrane Electrolyzers

Abstract: In order to adopt water electrolyzers as a main hydrogen production system, it is critical to develop inexpensive and earth-abundant catalysts. Currently, both half-reactions in water splitting depend heavily on noble metal catalysts. This review discusses the proton exchange membrane (PEM) water electrolysis (WE) and the progress in replacing the noble-metal catalysts with earth-abundant ones. The efforts within this field for the discovery of efficient and stable earth-abundant catalysts (EACs) have increase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 214 publications
(287 reference statements)
0
50
0
Order By: Relevance
“…This significant constraint could be somewhat alleviated using other electrolyzers with lower content of noble metals such as alkaline electrolyzers ( Sankir and Sankir, 2017 ), but the energy efficiency would decrease. Platinum is a known limitation to the growth of the water electrolysis industry ( Sealy, 2008 ) and in the last few years a significant amount of research has been directed at finding alternatives to the use of noble metals in electrolyzers, but there are few viable alternatives as of now ( Sun et al., 2018 ). In contrast, the materials typically used to catalyze the WGS reaction include iron, chromium, copper, aluminum and zinc, which are far more common natural resources, and different combinations of these and others can be used ( Pal et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…This significant constraint could be somewhat alleviated using other electrolyzers with lower content of noble metals such as alkaline electrolyzers ( Sankir and Sankir, 2017 ), but the energy efficiency would decrease. Platinum is a known limitation to the growth of the water electrolysis industry ( Sealy, 2008 ) and in the last few years a significant amount of research has been directed at finding alternatives to the use of noble metals in electrolyzers, but there are few viable alternatives as of now ( Sun et al., 2018 ). In contrast, the materials typically used to catalyze the WGS reaction include iron, chromium, copper, aluminum and zinc, which are far more common natural resources, and different combinations of these and others can be used ( Pal et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In their pioneering work, the authors concluded that the lowest Pt loading in a PEMFC for both negatrode and positrode electrodes equals to 0.35 mg/cm 2 , which translates to 3 kW per gram of platinum. Such values are also realistic for PEMWEs as indicated by our extensive review on PEM water electrolyzers [188].…”
Section: Mixed Electron-proton Conducting Composite Membranes For mentioning
confidence: 99%
“…Speaking of hydrogen reactions, Davydova and coworkers [7] used three-electrode rotating disc electrode experiments to show that Fe, Co, and Cu-doped Ni can have very high hydrogen oxidation reaction activity in alkaline media. Finalizing the discussion on catalysts is a thorough review by Sun et al [8], which discussed state-of-the-art PGM-free catalysts for PEM electrolyzers, giving an important perspective on activity, cost, and stability. This review is extremely fundamental and thorough, and it provides an excellent starting point for new researchers in this field to understand what was done and what can be done in the future.…”
mentioning
confidence: 99%